Synthesis, molecular modeling and antiviral activity of novel 5-fluoro-1H-indole-2,3-dione 3-thiosemicarbazones - Sevincli, Zekiye Seyma; Duran, Gizem Nur; Ozbil, Mehmet; Karali, Nilgun (Academic Press Inc Elsevier Science, 2020)
In this work, novel 5-fluoro-1-methyl/ethyl-1H-indole-2,3-dione 3-[4-(substituted phenyl)-thiosemicarbazones] 6a-n and 7a-n were synthesized. The antiviral effects of the compounds were tested against HSV-1 (KOS), HSV-2 (G) HSV-1 TK- KOS ACV(r) and VV in HEL cell cultures using acyclovir and ganciclovir as standards, and Coxsackie B4 virus in Vero cell cultures using ribavirin and mycophenolic acid as standards. R-2 ethyl substituted 7 derivatives were found effective against viruses tested. R-1 4-CF3 substituted 7d, R-1 4-OCH3 substituted 7 g and R-1 3-Cl substituted 7 l showed activity against HSV-1 (KOS), HSV-2 (G) HSV-1 TK- KOS ACVr and VV. Whereas only R-1 4-Br substituted 7n has selective activity against coxsackie B4 virus. Molecular modeling studies of 7d and 7l were performed to determine binding side on HSV-1 glycoprotein B and D, HSV-2 glycoprotein B structures.
Keywords: Synthesis; Antiviral activity; Thiosemicarbazones; 5-Fluoro-1H-indole-2,3-diones; Molecular modeling